The performance of the Securities Exchange of Barbados - Craigwell, Roland C. (1999)
Examines the performance of the Securities Exchange of Barbados (SEB) over the period 1987 to 1997. Discusses the aggregate stock market indicators and tests the efficiency of the SEB. Studies the relationship between the stock market and the economy.